Complementary feeding practices of children (6 months-23 months) in and around Lucknow, India - Srivastava, Geetika; Bhatnagar, Shrish; Khan, Kabeer Ahmad (International Journal of Contemporary Pediatrics, 2017)
Background: According to infant and child mortality in India, levels trends and determinants the under 5 mortality rates (UFMR) of India is facing a steady decline but at this rate India could not meet its target of millennium development goal-4 (MDG-4), which aimed to reduced UFMR by 2/3rds between 1990 and 2015. Objective of the current study was to study the complementary feeding practices amongst children of age group 6 months to 23 months in Lucknow. Methods: In this prospective cross sectional study 256 mothers were interviewed over a period of 6 months at a referral care centre in Lucknow. Children of age groups 6-8 months, 9-11 months and 12-23 months attending the Paediatric OPD were included in the study. WHO anthropometric indices of nutritional status: weight-for-age, length-for-age and weight-for-length, expressed in standard deviation (SD) units (z-scores) were calculated. Information on feeding practices and various particulars of the study children were taken into account and the WHO Indicators for assessing infant and young child feeding practices were calculated. Complementary feeding index CFI was calculated using these WHO indicators. Results: In the study group 24% of the children were stunted, 38% were underweight and 35% were wasted. The CFI was seen to be low in 32%, medium in 61% and high only in 7% children. It was found that parental education had significant correlation with CFI. Weight for height was significantly associated with CFI (p=0.011). Conclusions: CFI is an important tool to target the lacunae in complementary feeding practices. The CFI scores directly correlate with the nutrition status of children thus targeting the determinants of CFI will bring a positive change in infant and young child feeding practices.